The risk of thyroid cancer in relation to residential proximity to nuclear power plants: a systematic review and meta-analysis - Susanna Abraham Cottagiri; Will King; Laura Rodriguez-Villamizar; Paul J. Villeneuve (Environmental Health)
Abstract Introduction Ionizing radiation is a human carcinogen, and there is a public concern but limited evidence that it increases the incidence of cancer among those who live near nuclear power plants (NPPs). Previous analyses of thyroid cancer in these populations have been inconsistent, and the last synthesis was published nearly a decade ago. To address these gaps, we undertook a systematic review and meta-analysis. Methods A search strategy was developed and applied to PubMed, Scopus, and Web of Science databases. A total of 2006 publications were identified, with 11 studies of thyroid cancer incidence that met the inclusion criteria. Study quality was assessed using the Office of Health Assessment and Translation (OHAT) tool. Summary risk estimates relating residential proximity to the NPPs and thyroid cancer were generated using a random effects model. Heterogeneity in the risk estimates was assessed for study features that included: distance to the NPP, study quality, and biological sex. Results The 11 studies were categorized as either highly (n = 8) or plausibly (n = 3) prone to bias, primarily due to the reliance on ecological study designs. The meta-analysis summary relative risk of thyroid cancer among those who live close to NPPs (defined by ≤ 25 km distance or jurisdictional areas (e.g., community, county) relative to those who lived further away was 1.09 (95% CI: 0.93–1.29). The risk estimates were higher for studies that modelled more proximal residential distances (≤ 5 km) to NPPs than larger distances (≤ 25 km and jurisdictional areas). We found that the summary risk (RR=1.29, 95% CI: 0.77-2.16) was stronger among those studies less prone to bias. A non-significant increased risk was found among both men and women, but there was no evidence of sex differences in risk. Conclusion Overall, the findings suggest that living near a nuclear power plant increases the risk of thyroid cancer. The small number of studies on this topic, and the finding of higher risks in studies less prone to bias highlights the need for better-designed studies.